Pengembangan Media Pembelajaran Video Animasi Membatik Teknik Jumputan - Desy Tri Inayah; Chytra Mahanani (Jurnal Ilmiah Profesi Guru (JIPG), 2022)
This study aims to: 1) produce learning media products for animation video batik jumputan technique and 2) determine the feasibility of learning media animation video batik jumputan technique. The research method used is Research and Development which refers to the Borg and Gall development procedure. This research includes 10 stages, namely: 1) observation and finding potential problems, 2) data collection, 3) initial product development, 4) design validation, 5) design revision, 6) product testing, 7) product revision, 8) trial use, 9) revision, and 10) mass production. The results of the large group trial of 20 people showed a percentage of 60% strongly agree, 39% agree and 1% disagree. This shows that the learning media for this batik animation video is suitable for use in the jumputan technique learning process.